Central African Republic : 2007 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance and Modification of Performance Criteria, and Financing Assurances Review; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report, 2008)
Central African Republic (C.A.R) showed satisfactory performance amidst difficult conditions under the Poverty Reduction and Growth Facility (PRGF) arrangement. Executive Directors commended the authorities' efforts to consolidate peace and security and pursue macroeconomic stabilization and structural reforms. Directors stressed that policies need to focus on accelerating growth and increasing the economy's resilience with the private sector playing an increasing role. They agreed with the need to continue with fiscal consolidation and noted the improvement in debt sustainability. They agreed that C.A.R had fulfilled the requirements to reach the decision point under the Enhanced HIPC Initiative and qualified debt relief.